Integrated Reservoir Characterization of the Goldwyer Formation, Canning Basin - Johnson, Lukman Mobolaji (Curtin University, 2019)
This study has used an integrated approach to characterise the Goldwyer shale in the Broome Platform, Canning Basin in terms of geochemical sweetspot identification and the potential to generate hydrocarbon. This was achieved through laboratory analysis and using sophisticated geostatistical techniques to predict the property distribution in areas with poor well control. Furthermore, burial history modelling was carried out with well constrained maturity controlling factors such as exhumation as well as basin specific kinetics.